2022
DOI: 10.52538/iduhes.1037787
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Violence of Health Workers and Reasons of Violence from the Perspective of Health Workers

Abstract: Purpose: The aim of our study is to determine the status of violence of health workers and reasons of violence from the perspective of health workers. Methods: The sample of the study consisted of 244 healthcare workers who agreed to participate in the study. A data collection form containing personal information and opinions on violence, created by the researchers by scanning the literature, was used. The statistical analyses were conducted with the SPSS 21 package program. Results: The rate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…One of the dangers that nursing students are exposed to during clinical practice is violence. In the study conducted by Çakar, Şişman, Oruç (2019) [24], it was found that 13.3% of nursing students faced the threat of violence, and in the study conducted by Terkeş, Bedir, Değirmenci (2021) [25], it was found that one fourth of nursing students witnessed violence against health workers. Therefore, to prevent violence against healthcare workers, nursing students should know the code white application.…”
Section: Discussionmentioning
confidence: 99%
“…One of the dangers that nursing students are exposed to during clinical practice is violence. In the study conducted by Çakar, Şişman, Oruç (2019) [24], it was found that 13.3% of nursing students faced the threat of violence, and in the study conducted by Terkeş, Bedir, Değirmenci (2021) [25], it was found that one fourth of nursing students witnessed violence against health workers. Therefore, to prevent violence against healthcare workers, nursing students should know the code white application.…”
Section: Discussionmentioning
confidence: 99%